A Goal Programming Optimisation of Machining Parameters during the Production of Ti-Alloy Components on the CNC Lathe - Tayisepi, Nicholas; Madyira, Daniel M; Tawanda, Trust; Mugwagwa, Lameck (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
This experimental study, presents results of goal programming forecasting and optimising Ti6Al4V alloy components cutting conditions. During machining the optimising challenge concerns desirability of minimalising power consumption; cutting tool wear and cutting forces whilst simultaneously realising elevated material removal rate and advancing workpiece surface quality. Cutting process parameters optimisation is essential contemplation triggering proficient manufacturing activities enhancing competitiveness. Harmonising the miscellany machining conditions such that these contradictory intentions are, simultaneously, tackled portends well for sustainability of the machining activity. In this research, outside cutting tests were carry out, on the lathe machine, with coated carbide tipped tools at various parameter setting levels. Cutting speed and feed rate were characterised against dependent factors. Mathematical Modeling, was carried out in Minitab 22.1 Software. The models were uploaded on goal programme optimiser, LINDO/LINGO software, to predict the appropriate cutting parameters for a determinate machining situation. Goal Programme simulation results, with the performance factors equally weighted, produced optimum cutting parameters, vc = 227 mmin-1 and fn = 0.2416 mmrev-1. Validation experiments confirmed applicability of goal modeling in machining planning parameter prediction. Results showed fidelity of goal programming consistency as forecasting tool for titanium cutting parameters on the CNC lathe. Future research is delineated.